Detection of intracranial hemorrhage on CT scan images using convolutional neural network - Rahman, Afridi Ibn; Bhuiyan, Subhi; Reza, Ziad Hasan; Zaheen, Jasarat; Khan, Tasin Al Nahian (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.